Duzijanca: the celebration of ending the harvest as cultural practice and expression of identity - Černelić, Milana (2011)
The paper deals with specific cultural manifestation of the Croat ethnic group Bunjevci in Serbia (county of Voivodina), the celebration of the ending of the harvest called duzijanca. As part of their cultural heritage it celebrates the sucessful finishing of the harvest being shared by the family members and the reapers, embued with religious dimension, giving thanks to God for the collected crop. Blasko Rajic, the priest in the st. Roko Church in the town of Subotica, brought it into life again and fostered its celebration as the public event in 1911. Since then it continuously exists with occasional ups and downs. Since 1968. it became a public manifestation of the ethnic group Bunjevci and the town of Subotica in various forms and contents during the summer months. It was a separate church and civil celebration up to the 1993. when both aspects of the celebration have been united and enriched with new cultural contents. The paper shortly presents the duzijanca as an public manifestation through historical and contemporary perspective and outlines through a holistic view how the sense of place is embedded in the variety of social, cultural, religious, political and environmental context within which the event is celebrated. It also aims to give the answer in what way is this manifestation, both in past and present, the expression of the identity of the ethnic group Bunjevci in the multicultural environment of the county of Voivodina.